2010
DOI: 10.2214/ajr.09.3636
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Relative Wash-In Ratio of Adrenal Lesions at Early Biphasic CT

Abstract: Relative percentage wash-in ratio may help in differentiating adenoma from metastasis and in guiding the decision to perform CT directed at the adrenal glands when unenhanced CT is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
3
21
1
Order By: Relevance
“…Our results show that the probability of a lesion with a type 1 PE being an adenoma was 90.9%. Chung et al (15) and Foti et al (20) evaluated malignant adrenal lesions and found that none exhibited the peak of enhancement in the arterial phase. However, it is recognized that hypervascular nonadenomas, including pheochromocytoma, metastases from hypervascular extra-adrenal primary malignancies such as renal cell carcinoma or hepatocellular carcinoma, and primary adrenal carcinomas, may show a type 1 PE (10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the probability of a lesion with a type 1 PE being an adenoma was 90.9%. Chung et al (15) and Foti et al (20) evaluated malignant adrenal lesions and found that none exhibited the peak of enhancement in the arterial phase. However, it is recognized that hypervascular nonadenomas, including pheochromocytoma, metastases from hypervascular extra-adrenal primary malignancies such as renal cell carcinoma or hepatocellular carcinoma, and primary adrenal carcinomas, may show a type 1 PE (10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…When enhancement characteristics of an adrenal lesion are evaluated at CT, the imaging study should ideally include nonenhanced, portal venous (60-75 sec), and delayed (15 min) phases. Studies have shown that calculations that use the arterial phase are less sensitive and less specific than widely used washout calculations (33,34), and arterial phase scans are therefore not recommended as part of routine dedicated adrenal protocols. Washout is calculated at adrenal CT by using two different formulasabsolute washout and relative washout ( Table 2).…”
Section: Adrenal Adenomasmentioning
confidence: 99%
“…Benign lesions may have patent vessels that allow for easy contrast passage and exhibit fast wash-in and wash-out from the arterial to portal phases. Malignant lesions have a high cellular density and densely packed vessels, causing higher resistance to contrast flow and slow wash-in and wash-out patterns [18] . The drawback is that there is some overlap in contrast-enhancement patterns between adenomas and non-adenomas; therefore, wash-in patterns are not always reliable [19] .…”
Section: Ctmentioning
confidence: 99%
“…These non-FDG agents currently have limited clinical roles; thus, the focus in this section is on 18 F-FDG-PET examinations.…”
mentioning
confidence: 99%